Evaluation of probiotic and vaginal Lactobacillus species for the treatment of bacterial vaginosis and promotion of vaginal health in South African women - Happel, Anna-Ursula (Division of Medical Virology, 2022)
Background: Bacterial vaginosis (BV) increases women's risk for adverse reproductive outcomes and acquisition of sexually transmitted infections (STIs), including HIV. The etiology of BV is still unclear, and it has been hypothesized that lytic or temperate Lactobacillus bacteriophages may contribute. The current standard of care for BV are antibiotics like metronidazole or clindamycin, although these are not effective long-term, as rates of BV recurrence are high. There is thus an urgent need for durable treatment of BV to be developed. Probiotics administered adjunctively to antibiotics may improve efficacy and durability of BV treatment, but no randomized trial comparing antibiotic treatment to probiotics as an adjunct to antibiotics has been performed in South Africa, despite BV rates >50%. The South African Health Products Regulatory Authority (SAHPRA) regulates drugs and health supplements, into which probiotics are categorized locally. However, no probiotic product has yet been registered with SAHPRA. Further, there have been no recent surveys of the availability of probiotics for vaginal health in South Africa; neither has their suitability to be used in the treatment for BV been evaluated. Aims: The specific aims of this dissertation were (1) to survey the South African probiotic market and evaluate locally available products marketed explicitly for vaginal health in vitro, (2) to determine the efficacy of the most promising local overthe- counter (OTC) probiotic for vaginal health for BV treatment in South African women in a pilot randomized clinical trial that is approved by the regulatory authorities in South Africa, in order to explore the local regulatory landscape for future trials; (3) to screen and thoroughly characterize vaginal Lactobacillus strains isolated from healthy South African women in vitro for the development of a geographically-specific probiotic for vaginal health; and (4) to evaluate the role of bacteriophages in the etiology of BV and Lactobacillus spp. survival in vitro. Approach and results: To review probiotics available on the South African retail market, a cross-sectional survey using two-stage cluster sampling was conducted in Durban and Cape Town. Of the 104 unique probiotic products identified, only four were explicitly for vaginal health, although they contained bacterial species commonly found in the gastro-intestinal tract (GIT) and not lower female genital tract (FGT). The probiotics marketed for vaginal health were analysed for the bacterial contents, concentration per dose, growth kinetics, influence of bacterial growth on culture pH, adhesion to cervical cells, production of L-and D-lactic acid as well as H2O2, inhibitory activity against G. vaginalis and P. bivia and Group B Streptococcus (GBS), their susceptibility to antibiotics, and mucosal safety (using cytokine biomarkers). Batch testing revealed that they mainly contained the bacterial species and dose as claimed by the manufacturers. The contained bacterial isolates had promising probiotic characteristics, but there was some variability in the biological characteristics of isolates from different lot numbers of some of the products. A single-blind, randomised SAHPRA-approved trial enrolling BV positive, STI negative (including discharge-causing STIs; C. trachomatis, T. vaginalis, M. genitalium and A. vaginae) South African women was initiated to compare standard of care (SOC, MetroGelTM V, n=20) to a combination of metronidazole and a commercially-available probiotic (Vagiforte® PLUS Combo Pack, containing L. rhamnosus, L. acidophilus, B. longum and B. bifidum in oral capsules and vaginal spay, treatment duration 15 days) marketed for vaginal health, including treatment of BV and vaginal thrush, in South Africa (n=30, intervention group). The primary endpoint of the pilot study was BV cure one month after treatment completion. BV was assessed by Nugent scoring, vaginal pH was measured, IL-1α concentrations in cervicovaginal fluid were measured by ELISA as a biomarker of genital inflammation, and quantitative PCR (qPCR) was performed to measure the abundance of several vaginal Lactobacillus spp. (including L. crispatus, L. gasseri, L. jensenii, L. vaginalis, L. mucosae and L. iners), in addition to key BV-associated bacteria (including G. vaginalis, P. bivia, A. vaginae, BVAB2 and Megasphaera 1), the bacterial species contained in Vagiforte® (including L. acidophilus, L. rhamnosus, B. bifidum and B. longum) and Candida spp. (including C. albicans, C. dubliniensis, C. glabrata, C. krusei, C. lusitaniae, C. parapsilosis, and C. tropicalis), as a common side effect of metronidazole treatment is vaginal thrush. An interim analysis of the first 24 participants who have completed the trial is included in this dissertation, as the trial is still ongoing. The probiotic was found to be well accepted and no product related adverse events were reported, although women commonly experienced vaginal Candida infections after topical metronidazole use. In the interim analysis, BV cure rates were similar between the SOC and intervention group, as was vaginal pH and the abundances of Lactobacillus spp. and most BV-associated bacteria. Women randomized to the intervention group had higher levels of B. bifidum and B. longum after treatment, which tended to go along with increased levels of Candida spp. and some BV-associated bacteria, while L. crispatus levels were lower in these women. This shows the urgent need to develop a vaginal probiotic containing Lactobacillus strains that are commensal to the FGT, to ensure achieving the desired effect of adjunctive probiotics in BV treatment. Thus, the characteristics of the commercially in South Africa available probiotic strains were compared to clinical vaginal Lactobacillus strains isolated from healthy South African women. A weighted scoring system was developed to select candidate strains for the development of a vaginal probiotic. Towards this aim, 57 Lactobacillus strains were isolated from healthy South African women (including 10 L. crispatus, 9 L. gasseri, 18 L. jensenii, 8 L. vaginalis, and 12 L. mucosae strains) which were distinct to the commercially available probiotic strains, and several isolates exhibited better probiotic characteristics in vitro than the commercially available probiotic bacterial strains (such as ability to lower pH and adherence to cervical cells), although this appeared to be highly strain- and not species specific. Based on weighted scores, two L. crispatus, two L. jensenii, and one L. vaginalis and one L. gasseri strain isolated from BV and STI negative South African women were selected for the development of a local probiotic for vaginal health. The presence of bacteriophages that target vaginal Lactobacillus spp. in cervicovaginal secretions of women with and without BV was evaluated using serial bacteriophage transfer and plaque assays. No lytic bacteriophages that targeted vaginal Lactobacillus spp. (including L. crispatus, L. gasseri, L. jensenii, L. vaginalis and L. mucosae) were isolated from FGT secretions, although CRISPR loci were common in publically available full Lactobacillus genome sequences. However, temperate bacteriophages were induced from the majority (71.8%) of the clinical Lactobacillus strains and 61.1% of the probiotic Lactobacillus strains screened using Mitomycin C, which was confirmed by transmission electron microscopy. Based on their morphology, these Lactobacillus bacteriophages belonged to the families of Sipho-, Myo- and Podoviridae. Conclusions: There are very few probiotics for vaginal health on the South African market, and the development of a probiotic containing commensals of the lower FGT should urgently be considered. Lytic bacteriophages targeting Lactobacillus spp. were not found in this study, although temperate bacteriophages were common and could influence Lactobacillus survival in vivo. Screening women with vaginal discharge for the SAHPRA-acknowledged pilot probiotic trial of Vagiforte PLUS® confirmed a high burden of STIs in Cape Town, South Africa, and that the symptom vaginal discharge is a very poor predictor for BV. The pilot trial showed that large doubleblind, randomized, placebo-controlled trials with adequate screening and enrolment algorithms and sample sizes, using a product containing vaginal Lactobacillus spp., are needed to determine the efficacy of adjunctive probiotics on BV cure and recurrence in South African women. Finally, while the products currently being marketed for vaginal health in South Africa and worldwide mostly do not contain Lactobacillus spp. commonly found in the lower FGT, several promising candidates from the FGTs of healthy, young, HIV- and BV- South African women were isolated and characterized that may prove more efficacious in treating BV. These have the potential to make a big impact on reproductive outcomes and HIV risk in young South African women.